The Development of Thematic Board Educational Game Tools to Train The Literacy Skills of Children 5-6 Years Old - Safitri, Nita Dwi; Hasanah, Uswatun; Masruroh, Farhatin; Khulusinniyah, Khulusinniyah; Dodd, Jaime (Indonesian Journal of Early Childhood Educational Research (IJECER), 2022)
The absence of thematic board educational game tools motivates this research to train the literacy skills of children aged 5-6 years. This study aims to determine the development and feasibility of thematic board educational game tools to improve the literacy skills of children aged 5-6 years. The research method used is Research and Development (R&D) which adopts the Borg and Gall development stages. The results of this research and development are: 1) Development of the thematic board educational game tool through several stages, namely: a) seeing potential and problem identification b) research and data collection, c) product design e) product revision, d) validation and trial phase small scale and large scale. The results of the validation of the material experts prove 2 with a category is very feasible. The average media expert validation assessment is the very feasible category. The assessment of small class trials in the very feasible category, large-scale trials in the very feasible category. The average teacher response questionnaire is in the very feasible category.